In vivo measurement of attenuation coefficient of blood in a dorsal hand vein in a frequency range of 10–45 MHz: A preliminary study - Arakawa, Mototaka; Higashiyama, Kyohei; Mori, Shohei; Yashiro, Satoshi; Ishigaki, Yasushi; Kanai, Hiroshi (Frontiers in Physics, 2023)
In this study, the attenuation coefficient of blood was measured in vivo in the frequency range of 10–45 MHz. A procedure to correct the distribution of sound pressure in the measurements was discussed. Further, in vivo measurements were applied on the dorsal hand vein of four healthy subjects at rest and during avascularization. As a preliminary result, less variation of the measured attenuation coefficients was achieved by the proposed method. The comparable results of the inclination of the attenuation coefficients were obtained at rest and during avascularization. Furthermore, the attenuation coefficients during avascularization were markedly higher than those at rest, reflecting the degree of red blood cell aggregation promoted by avascularization. This method may aid in the noninvasive evaluation of blood properties reflecting the degree of red blood cell aggregation.